METHODS OF CORRECTION OF BIOCHEMICAL CHANGES IN THE BODY OF ANIMALS IN THE DEVELOPMENT OF CHRONIC NITRATE-NITRITE TOXICOSES. - Леськів, Х. Я. (Scientific Progress & Innovations, 2013)
The effects of nitrate load on the biochemical blood of pigs were disclosed, as well as methods of correction of the pathogenesis of toxicity in antioxidants were proposed. The use of methionine, fenaron and metifen at pigs in the development of nitrate-nitrite toxicity contributed to the normalization of morphological and biochemical parameters of blood of experimental pigs. Best normalizing effect on the body of pigs, which carried nitrate load metifen showed a dose of 0.9 mg/kg.